2018
DOI: 10.1016/j.soildyn.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Removable friction dampers for low-damage steel beam-to-column joints

Abstract: Beam-to-column joints equipped with friction dampers are promising solutions to improve the performance of steel moment resisting frames due to the possibility to guarantee large dissipation capacity limiting the structural damage under severe seismic conditions. In this paper, the experimental tests and the numerical simulations of two types of joints are shown and discussed with the aim of developing pre-qualified configurations. The friction dampers are designed to be easily removable from both the lower be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Latour et al developed a new friction damper composed of friction plates with different materials from the proposed studies, 15 and its seismic performance was validated through an experimental campaign. Also, Latour et al designed an easily removable friction damper for low-damage steel beam-to-column joints, 16 and the experimental tests and numerical simulations were discussed. For the purpose of minimizing the destruction of the multistory hybrid timber-steel structures after severe earthquakes, Hashemi et al presented a hybrid damage avoidant steel-timber wall system using the innovative resilient slip friction (RSF) joint.…”
Section: F I G U R E 2 Commonmentioning
confidence: 99%
“…Latour et al developed a new friction damper composed of friction plates with different materials from the proposed studies, 15 and its seismic performance was validated through an experimental campaign. Also, Latour et al designed an easily removable friction damper for low-damage steel beam-to-column joints, 16 and the experimental tests and numerical simulations were discussed. For the purpose of minimizing the destruction of the multistory hybrid timber-steel structures after severe earthquakes, Hashemi et al presented a hybrid damage avoidant steel-timber wall system using the innovative resilient slip friction (RSF) joint.…”
Section: F I G U R E 2 Commonmentioning
confidence: 99%
“…One of the most commonly used low damage connections is friction connection and it has been studied by many scholars. The sliding hinge joint (SHJ) beam-column friction connection which is known as asymmetric friction connection (AFC) was proposed by Clifton [ 8 ] for the first time ( Figure 1 [ 9 ]) and it has been further developed by many scholars [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. This kind of AFC beam-column connection generally uses friction damper to replace the traditional rigid structure connections.…”
Section: Introductionmentioning
confidence: 99%
“…Low-damage seismic resistant connections, such as sliding hinge joints and asymmetric friction connections with friction interfaces made of brass, steel or aluminum were subsequently investigated [22]. Presently, a novel configuration friction kit was employed containing removable haunches or ribs with slotted holes, and stainless steel friction pads were horizontally or vertically equipped together with L-stubs at the lower beam flange (based on [23]), aiming to detach the friction dampening device from both the bottom beam flange or the column surface and thus simplify the reparability. The results demonstrated that the rotation action of the beam around the pin at the top T-stub had a promising energy concentration as a result of the detachable friction damper, as well as negligible plastic deformation in other components; however, the disadvantage of occupying available height cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%